Systematic agronomic farm management for improved coffee quality - Läderach, Peter R.D.; Oberthür, Thomas; Cook, Simon E.; Estrada Iza, M; Pohlan, J; Fisher, M.; Rosales Lechuga, R. (Elsevier, 2011)
There is growing interest of international markets in differentiated agricultural products from the tropics. Coffee is a tropical crop of relatively high quality, whose value is increasing as consumer demand in developed countries for specialty coffee. Smallholders in emerging markets can benefit by capitalizing on the natural resource variability in their production system and from the knowledge that they have about this variability. The objective of this paper is to illustrate the benefits of systematically targeting management practices by coffee growers to improve attributes of their product. Data from case studies in Colombia and Mexico show statistically significant differences in beverage quality of coffees grown under different production conditions such as slope aspect, varieties, times of harvest, and shade levels. Possible intervention options can be selected by growers in terms of their ease of implementation, the likely improvement of quality that they achieve and the resource intensiveness they require. The conclusion is that optimum management is site specific so that it is not possible to make any blanket recommendations. Using continuous management cycles of implementation, observation, interpretation and evaluation the site specificity provides growers an opportunity to improve management over time to produce a higher quality product.